CONTRIBUIÇÕES DA SALA DE AULA INVERTIDA PARA O ENSINO DE FÍSICA: UM ESTUDO NO ENSINO MÉDIO À LUZ DA TEORIA DA APRENDIZAGEM SIGNIFICATIVA - Deponti, Maria Aparecida Monteiro (2020)
The present work is the result of a doctoral research that presents as main objective to verify the contributions of the Inverted Classroom (IC) methodology planned from the perspective of the Three Pedagogical Moments (TPM), with the use of Information and Communication Technologies (ICT), in physics teaching, to effect significant learning on concepts of Mechanical Energy in high school. The research was developed with students of the 1st year of the Technical Course integrated to the High School in Renewable Energy Systems of the Federal Institute Farroupilha, Jaguari Campus/RS. At first, evidence of significant learning was found with an experimental group of students with which a Teaching Unit (TU) was developed to address Mechanical Energy concepts and implement the IC methodology according to the TPM, together with the use of ICT. In a second moment, the same concepts were approached using the traditional teaching methodology with a group of students called control. The control group was used as a parameter to search for evidence of significant learning in the experimental group. For this purpose, the necessary data collection instruments were used: pre-test and post-test questionnaires, field diary, audio and image records, records of students' interactions with the virtual learning environment, students' lesson material. The research, with a quali-quanti approach, was based on Ausubel's Theory of Meaningful Learning (1978) and Bergmann and Sams's Inverted Classroom Model (2007). For the qualitative analysis of content, assumptions of the five stages of Moraes (1999) were followed and for quantitative analysis the t-Student de Gosset statistical test (1908) was used. Data analysis, using the criteria previously established for the research, showed evidence of the students' learning occurrence. The results of the t-Student test pointed to a significant conceptual evolution of the students of the experimental group in relation to the concepts of Mechanical Energy that were worked throughout the TU. The methodological path adopted highlighted the importance of the TU organization with a view to implementing the IAS, which had the activities organized in TPM, for the teaching-learning process and also to promote and facilitate meaningful learning of the concepts worked. In the context presented, the IC, was an active methodology that contributed to the promotion of subsunçores and/or construction of previous organizers on mechanical energy concepts and favored the learning of these concepts significantly. It is concluded that the implementation of the IC requires the promotion of teaching situations that allow students to contextualize knowledge, peer collaboration and protagonism of the students to contemplate meaningful learning.